MOVING for Health: Connecting Physical Literacy and Health Literacy in Four Settings (Schools, Sports Clubs, Communities, Health Centres) (Baltic Journal of Sport and Health Sciences, 2026)
The EU-funded “MOVING for Health” (MfH) project aims to connect physical and health literacy by offering tools, knowledge, and information to promote healthy lifestyles. Since no existing model fully integrates these two literacies, the project addresses this gap by connecting individuals (teachers, trainers, health providers, community developers) and organisational settings (schools, sports clubs, health centres, local communities).The purpose of the project was to connect physical and health literacies, develop a MOVING for Health model and test the model through a cohort of experienced practitioners from four settings (schools, sports clubs, health centres, and local communities) in Sweden, Spain, and Slovenia.The MfH initiative was developed based on research and analysis of existing resources, good practices, and principles in the fields of health and physical literacy. These principles acted as basis for the development of an online training tool allowing practitioners to use the tool in four languages: English, Spanish, Slovenian, and Swedish. The tool supports a holistic approach to HEPA promotion, equipping practitioners with skills to support students/pupils, clients/patients, sports club members, and citizens.The MfH model is currently being tested in three countries (Slovenia, Spain, and Sweden) and in four different settings (schools, sports clubs, health centres, and local communities) to assess how it is understood. The results will provide evidence-based insights that can inform future HEPA policies at both national and European levels.While a European network of project partners has already been established, efforts continue to expand this network across Europe to exchange knowledge and experiences.Through international testing of the online tool, the project offers practical guidance for both practitioners and policymakers. Key outcomes include a research report, guiding principles, good practices, a training tool, and an online platform to support ongoing collaboration and knowledge sharing: https://movingforhealth.isca.org/project.